Recent advances in AIDS-related cryptococcal meningitis treatment with an emphasis on resource limited settings. Issue 4 (3rd April 2017) - Lofgren, Sarah; Abassi, Mahsa; Rhein, Joshua; Boulware, David R
ABSTRACT: Introduction : Recent advances in the treatment and prevention of cryptococcal meningitis have the potential to decrease AIDS-related deaths. Areas covered : Targeted screening for asymptomatic cryptococcal antigenemia in persons with AIDS is a cost effective method for reducing early mortality in patients on antiretroviral therapy. For persons with symptomatic cryptococcal meningitis, optimal initial management with amphotericin and flucytosine improves survival compared to alternative therapies; however, amphotsericin is difficult to administer and flucytosine has not been available in middle or low income countries, where cryptococcal meningitis is most prevalent. Expert commentary : Improved care for cryptococcal meningitis patients in resource-limited settings is possible, and new treatment possibilities are emerging.